2002
DOI: 10.3386/w8754
|View full text |Cite
|
Sign up to set email alerts
|

Why has the Employment-Productivity Tradeoff among Industrialized Countries been so strong?

Abstract: This paper is motivated by a set of cross-country observations on labor productivity growth among industrial countries over the period . In particular, we show that over this period, the speed of convergence among industrialized countries has decreased substantially while the negative effect of a country's own employment growth (or labor force growth) on labor productivity has increased dramatically. The main contribution of the paper is to show how these observations are consistent with the view that industri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 16 publications
(28 reference statements)
1
38
1
2
Order By: Relevance
“…For OECD countries, we have examined the potential biases induced by not taking into account differences across countries in participation rates. We found that using a direct measure of number of workers for OECD countries provides even stronger evidence in favor of the main claim of the paper than that found using population data (see Beaudry and Collard [2002]). Figure 1 reports the distribution of (log) output per worker across the set of NSSA countries in 1960 and 1998.…”
Section: Changes In Distribution 1960-98mentioning
confidence: 36%
See 1 more Smart Citation
“…For OECD countries, we have examined the potential biases induced by not taking into account differences across countries in participation rates. We found that using a direct measure of number of workers for OECD countries provides even stronger evidence in favor of the main claim of the paper than that found using population data (see Beaudry and Collard [2002]). Figure 1 reports the distribution of (log) output per worker across the set of NSSA countries in 1960 and 1998.…”
Section: Changes In Distribution 1960-98mentioning
confidence: 36%
“…We also explored window sizes between 15 to 25 years, all of which led to similar conclusions. In Beaudry and Collard [2002] this approach was used to examine changes in the growth process among OECD country's. …”
Section: The Rise In Importance Of Accumulation Forcesmentioning
confidence: 99%
“…A temporary setback occurred during the Asian crisis in 1997/98, but it was corrected afterwards. Statistics in general show that (1) the labour productivity of the manufacturing sector has been increasing over time, (2) there are widespread mismatches among the share of manufacturing growth and the share of manufacturing employment, indicating a possible expansion of skilled employment.…”
Section: Resultsmentioning
confidence: 99%
“…Beaudry and Collard [2], for example, explain that reducing controls on trade causes a drastic technological change, and makes human capital the factor for determining the growth in labour productivity while also raising the demand for more skilled workers. Davis and Harrigan [5] explained that trade liberalisation and productivity have been found to be biased toward skilled workers.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic of labour demand is the big diversification according to the sectoral, spatial and professional structures [Batóg et al 2016]. The share of labour in the national product that depends on the level of labour productivity, minimal wage and hours worked influences the number of employed persons as well as the number of unemployed persons [Beaudry and Collard 2002;Izyumov and Vahaly 2014: 697].…”
Section: Introductionmentioning
confidence: 99%